Carbon-coated lithium iron phosphate, preparation method thereof and lithium battery
By mixing the fullerene solution with the iron phosphate precursor and ball milling with the lithium source, metal ion dopant and carbon source, the poor conductivity of lithium iron phosphate materials is solved, and the battery energy efficiency and powder resistance are improved are achieved. The effect is suitable for large-scale production.
Patent Information
- Application Number
- CN202411666025.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The powder resistance of lithium iron phosphate materials is relatively high and the conductivity is poor, resulting in low discharge energy efficiency of the battery and cannot meet the battery design requirements. In the existing carbon coating technology, the carbon source has a low degree of graphitization and relatively high conductivity. Difference.
The fullerene solution is mixed with the iron phosphate precursor for drying, and then ball milling is performed with lithium source, metal ion dopants and carbon source, and sintered under a protective atmosphere to form carbon-coated lithium iron phosphate to improve its conductivity and Energy efficiency.
It effectively reduces the powder resistance of lithium iron phosphate material, improves the energy efficiency of the battery, and is simple in the method, low in price of raw materials, suitable for large-scale production, and has uniform particle size and good crystallinity.
Smart Images

Figure CN119297254A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a carbon-coated lithium iron phosphate and a preparation method thereof, and a lithium battery. Background Art
[0002] At present, the powder resistance of lithium iron phosphate material is relatively high and the conductivity is poor. The discharge energy efficiency of the batteries made from it is relatively low and cannot meet the design requirements of the battery cells, resulting in an increase in the defective rate of the battery cells.
[0003] In the synthesis process of lithium iron phosphate, adding carbon source for carbon coating can reduce the powder resistance of the material, thereby improving the discharge energy efficiency of the battery. However, in the current lithium iron phosphate carbon coating technology, the carbon source is mostly a combination of organic carbon source and inorganic carbon source, and the graphitization degree of the carbon source is low, and the conductivity is poor. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems: the powder resistance of lithium iron phosphate material is relatively high, the conductivity is relatively poor, and the discharge energy efficiency of the battery is relatively low. In the current carbon-coated lithium iron phosphate, the graphitization degree of the carbon source is low and the conductivity is relatively poor.
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a carbon-coated lithium iron phosphate and a preparation method thereof, and a lithium battery, which can improve the conductivity of the carbon-coated lithium iron phosphate material, reduce the powder resistance of the material, and improve the energy efficiency of the battery.
[0006] An embodiment of the present invention provides a method for preparing carbon-coated lithium iron phosphate, comprising the following steps:
[0007] (1) mixing an iron phosphate precursor and a fullerene solution, and then drying the mixture to obtain a fullerene-coated iron phosphate precursor; wherein the solvent of the fullerene solution is a non-aqueous solvent;
[0008] (2) mixing the fullerene-coated iron phosphate precursor, a lithium source, a metal ion dopant and a carbon source and ball milling the mixture to obtain a mixture, and drying the mixture; the metal ion dopant includes a metal doping element;
[0009] (3) Sintering the dried mixture under a protective atmosphere to obtain carbon-coated lithium iron phosphate.
[0010] Advantages and technical effects brought by the preparation method of carbon-coated lithium iron phosphate of the embodiment of the present invention: Carbon-coated lithium iron phosphate can effectively improve the conductivity of lithium iron phosphate materials and reduce the powder resistance of materials, thereby improving the energy efficiency of batteries. Compared with the related art of increasing the conductivity by adding conductive agents, the method of the present invention does not increase the powder resistance of materials and has little effect on the performance of batteries. The synthesis method of the present invention is simple, the raw material price is low, and the carbon-coated lithium iron phosphate material has uniform particle size and good crystallinity, which is suitable for large-scale production and is more practical and economical.
[0011] In the embodiment of the present invention, a ferric phosphate precursor and a fullerene solution are mixed to prepare a fullerene-coated ferric phosphate precursor. The solvent of the fullerene solution is a non-aqueous solvent. By utilizing the solubility characteristics of fullerene, the fullerene can be uniformly coated on the ferric phosphate precursor at the molecular level, and the fullerene SP can be fully utilized. 2 The conductivity of orbital hybridization improves the conductivity of lithium iron phosphate materials, reduces the powder resistance of materials, and improves the energy efficiency of batteries. If the iron phosphate precursor and fullerene are only physically mixed, it is difficult to coat them evenly; if the fullerene solution uses water as a solvent, the physical and chemical properties of fullerene and water are completely different, and the affinity between them is very weak. Too many water molecules will reduce their affinity and affect their own properties, resulting in performance degradation. Therefore, it is not suitable to mix the fullerene aqueous solution with the iron phosphate precursor.
[0012] In the embodiment of the present invention, a fullerene-coated iron phosphate precursor, a lithium source, a metal ion dopant and a carbon source are mixed and ball-milled, and the lithium source, the metal ion dopant and the carbon source are uniformly coated on the precursor, and after high-temperature sintering, the metal doping element is doped into the internal structure of the lithium iron phosphate, and the metal doping element in the lithium iron phosphate can replace the iron position, forming lattice distortion and other lattice defects, thereby improving the ionic conductivity and electronic conductivity of the carbon-coated lithium iron phosphate. The present invention additionally adds other carbon sources as reducing agents to participate in chemical reactions, and at the same time coats the lithium iron phosphate to enhance conductivity.
[0013] In some embodiments, in step (1), the solvent of the fullerene solution includes at least one of xylene, toluene or chlorobenzene.
[0014] In some embodiments, in step (1), the particle size of the iron phosphate precursor is 100-500 nm;
[0015] and / or, the mass ratio of the iron phosphate precursor to fullerene is 97-100:0.01-3;
[0016] And / or, the mixing is carried out under heating conditions; the mixing temperature is 40-80° C.; and the mixing time is 2-3 hours.
[0017] In some embodiments, in step (2), the molar ratio of the lithium element in the lithium source, the iron element in the fullerene-coated iron phosphate precursor, and the metal doping element in the metal ion dopant is 1.0-1.08: 0.95-0.99: 0-0.05;
[0018] And / or, in the mixture of the fullerene-coated iron phosphate precursor, the lithium source, the metal ion dopant and the carbon source, the mass percentage of the carbon source is 3%-10%;
[0019] And / or, the ball milling time is 3 to 7 hours.
[0020] In some embodiments, in step (2), the lithium source includes at least one of lithium hydroxide and lithium carbonate;
[0021] And / or, the carbon source includes at least one of glucose, phenolic resin, sucrose, citric acid, polyethylene glycol, and conductive carbon black.
[0022] In some embodiments, in step (2), the metal doping element includes at least one of aluminum, titanium, magnesium, and vanadium;
[0023] And / or, the metal ion dopant includes at least one of an oxide, a hydroxide, and a salt of a metal doping element.
[0024] In some embodiments, in step (3), the sintering temperature is 500-800°C;
[0025] And / or, the sintering time is 8-36h;
[0026] And / or, the particle size of the carbon-coated lithium iron phosphate is 0.3-2.0 μm.
[0027] In some embodiments, in step (3), the dried mixture is first pre-fired under a protective atmosphere, ground after cooling, and then sintered under a protective atmosphere; the pre-fired temperature is 500-600°C; the pre-fired time is 12-24h; the sintered temperature is 600-800°C; and the sintered time is 8-12h.
[0028] The embodiment of the present invention provides a carbon-coated lithium iron phosphate, which is prepared by the preparation method described in the embodiment of the present invention. In the embodiment of the present invention, the carbon-coated lithium iron phosphate has higher electrical conductivity and lower powder resistance, and can improve the energy efficiency of the battery.
[0029] The embodiment of the present invention provides a lithium battery, including a positive electrode material, wherein the positive electrode material includes the carbon-coated lithium iron phosphate according to the embodiment of the present invention. In the embodiment of the present invention, the carbon-coated lithium iron phosphate has higher electrical conductivity and lower powder resistance, and can improve the energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a Raman test image of the carbon-coated lithium iron phosphate according to Example 2 of the present invention.
[0031] Figure 2 It is a test diagram of the AC impedance of the embodiment of the present invention and the comparative example.
[0032] Figure 3 It is a charging and discharging curve diagram of the embodiment of the present invention and the comparative example.
[0033] Figure 4 It is a comparison chart of battery energy efficiency of the embodiment of the present invention and the comparative example.
[0034] Figure 5 It is a comparison chart of battery capacity retention rate between the embodiment of the present invention and the comparative example.
[0035] Figure 6 It is a comparison diagram of average discharge voltages at different rates between the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0037] A method for preparing carbon-coated lithium iron phosphate according to an embodiment of the present invention comprises the following steps:
[0038] (1) mixing an iron phosphate precursor and a fullerene solution, and then drying the mixture to obtain a fullerene-coated iron phosphate precursor; wherein the solvent of the fullerene solution is a non-aqueous solvent;
[0039] (2) mixing the fullerene-coated iron phosphate precursor, a lithium source, a metal ion dopant and a carbon source and ball milling the mixture to obtain a mixture, and drying the mixture; the metal ion dopant includes a metal doping element;
[0040] (3) Sintering the dried mixture under a protective atmosphere to obtain carbon-coated lithium iron phosphate.
[0041] The preparation method of the carbon-coated lithium iron phosphate of the embodiment of the present invention can effectively improve the conductivity of the lithium iron phosphate material and reduce the powder resistance of the material, thereby improving the energy efficiency of the battery. Compared with the related art of increasing the conductivity by adding a conductive agent, the method of the present invention does not increase the powder resistance of the material and has little effect on the performance of the battery. The synthesis method of the present invention is simple, the raw material price is low, and the carbon-coated lithium iron phosphate material has a uniform particle size and good crystallinity, which is suitable for large-scale production and is more practical and economical.
[0042] In the embodiment of the present invention, a ferric phosphate precursor and a fullerene solution are mixed to prepare a fullerene-coated ferric phosphate precursor. The solvent of the fullerene solution is a non-aqueous solvent. By utilizing the solubility characteristics of fullerene, the fullerene can be uniformly coated on the ferric phosphate precursor at the molecular level, and the fullerene SP can be fully utilized. 2 The conductivity of orbital hybridization improves the conductivity of lithium iron phosphate materials, reduces the powder resistance of materials, and improves the energy efficiency of batteries. If the iron phosphate precursor and fullerene are only physically mixed, it is difficult to coat them evenly; if the fullerene solution uses water as a solvent, the physical and chemical properties of fullerene and water are completely different, and the affinity between them is very weak. Too many water molecules will reduce their affinity and affect their own properties, resulting in performance degradation. Therefore, it is not suitable to mix the fullerene aqueous solution with the iron phosphate precursor.
[0043] In the embodiment of the present invention, a fullerene-coated iron phosphate precursor, a lithium source, a metal ion dopant and a carbon source are mixed and ball-milled, and the lithium source, the metal ion dopant and the carbon source are uniformly coated on the precursor, and after high-temperature sintering, the metal doping element is doped into the internal structure of the lithium iron phosphate, and the metal doping element in the lithium iron phosphate can replace the iron position, forming lattice distortion and other lattice defects, thereby improving the ionic conductivity and electronic conductivity of the carbon-coated lithium iron phosphate. The present invention additionally adds other carbon sources as reducing agents to participate in chemical reactions, and at the same time coats the lithium iron phosphate to enhance conductivity.
[0044] In some embodiments, a fullerene solution is used in step (1); optionally, the solvent of the fullerene solution includes at least one of xylene, toluene or chlorobenzene, and the xylene includes at least one of o-xylene, m-xylene and p-xylene; optionally, the concentration of the fullerene solution is greater than 5 g / L, specifically, for example, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L. In the embodiment of the present invention, the fullerene solution using xylene, toluene or chlorobenzene as solvent can uniformly coat the fullerene on the iron phosphate precursor at the molecular level, and can give full play to the fullerene SP 2 The conductivity of orbital hybridization improves the conductivity of lithium iron phosphate materials, reduces the powder resistance of materials, and improves the energy efficiency of batteries.
[0045] In some embodiments, in step (1), the fullerene comprises fullerene C 60 , the fullerene C 60 For closed fullerene.
[0046] In some embodiments, in step (1), the mass ratio of the iron phosphate precursor to fullerene is 97-100:0.01-3, specifically, 97-100 (e.g., 97, 98, 99, 100):0.01-3 (0.01, 0.1, 0.5, 1, 2, 2.5, 3). In the embodiment of the present invention, the mass ratio of the iron phosphate precursor to fullerene is 97-100:0.01-3, which is beneficial to reduce the resistivity. When the fullerene content is too low or not contained, the resistivity reduction effect is not good; when the fullerene content is too high, the carbon coating effect is affected.
[0047] In some embodiments, an iron phosphate precursor is used in step (1);
[0048] Optionally, the particle size of the iron phosphate precursor is 100-500 nm, specifically, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm;
[0049] The present invention has no special restrictions on the preparation method of the iron phosphate precursor. For example, the iron phosphate precursor is synthesized by a hydrothermal method; optionally, an iron source is reacted with a phosphorus source to obtain the iron phosphate precursor; the iron source includes at least one of ferric chloride, iron oxide, iron powder, ferrous oxalate, ferrous sulfate, and ferric nitrate; the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and ammonium monohydrogen phosphate; optionally, the iron source and the phosphorus source are in an equimolar ratio; optionally, the reaction temperature is 60-100°C;
[0050] In a specific embodiment, ferrous sulfate heptahydrate and ammonium dihydrogen phosphate solution in an equal molar ratio are weighed and added into a reaction kettle, mixed and stirred, and reacted to obtain an iron phosphate precursor.
[0051] In some embodiments, in step (1), an iron phosphate precursor and a fullerene solution are mixed;
[0052] Optionally, the mixing time is 2 to 3 hours;
[0053] Optionally, the mixing is performed under stirring;
[0054] Optionally, the mixing is performed under heating conditions; the mixing temperature is 40-80°C, specifically, for example, 40°C, 50°C, 60°C, 70°C, 80°C; the heating is performed in a water bath;
[0055] Optionally, an iron phosphate precursor is added to the fullerene solution;
[0056] Optionally, after mixing, filtering and washing are performed, and then drying is performed to obtain a fullerene-coated iron phosphate precursor; optionally, after drying, sieving is performed.
[0057] In the embodiment of the present invention, the iron phosphate precursor and the fullerene solution are mixed under heating conditions, which is beneficial to improving the mixing uniformity.
[0058] In some embodiments, in step (2), the molar ratio of the lithium element in the lithium source, the iron element in the fullerene-coated iron phosphate precursor, and the metal doping element in the metal ion dopant is 1.0-1.08:0.95-0.99:0-0.05; specifically, 1.0-1.08 (for example, 1.00, 1.02, 1.05, 1.08):0.95-0.99 (for example, 0.95, 0.96, 0.97, 0.98, 0.99):0-0.05 (for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05), optionally, 1.05:0.98:0.02. In the embodiment of the present invention, the molar ratio of lithium element, iron element and doping element is 1.0-1.08:0.95-0.99:0-0.05, which is conducive to the complete lattice of lithium iron phosphate grown and the appropriate grain size.
[0059] In some embodiments, in the step (2), in the mixture of the fullerene-coated iron phosphate precursor, the lithium source, the metal ion dopant and the carbon source, the mass percentage of the carbon source is 3%-10%, specifically, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. In the embodiment of the present invention, the addition of a traditional carbon source is beneficial to enhance the electronic conductivity.
[0060] In some embodiments, in step (2), the fullerene-coated iron phosphate precursor, lithium source, metal ion dopant, carbon source and dispersant are mixed and ball-milled; optionally, the dispersant includes water, preferably deionized water; the mass of the dispersant is 2-3 times the mass of the solid raw material, and the solid raw material includes the fullerene-coated iron phosphate precursor, lithium source, metal ion dopant and carbon source.
[0061] In some embodiments, in step (2), the ball milling time is 3 to 7 hours, specifically, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours.
[0062] In some embodiments, in step (2), the lithium source includes at least one of lithium hydroxide and lithium carbonate.
[0063] In some embodiments, in step (2), the carbon source includes at least one of glucose, phenolic resin, sucrose, citric acid, polyethylene glycol (PEG), and conductive carbon black.
[0064] In some embodiments, in step (2), the carbon-coated lithium iron phosphate includes a metal doping element; the metal doping element includes at least one of aluminum, titanium, magnesium, and vanadium; optionally, the metal ion dopant includes at least one of an oxide, hydroxide, and salt of the metal doping element; optionally, the salt is selected from a chloride, isopropoxide, or ammonium salt of the metal doping element. In an embodiment of the present invention, the metal doping element includes aluminum, titanium, magnesium, and vanadium, wherein titanium, vanadium, and iron are in the same period, have similar atomic radii, and are easy to occupy the iron position in the lattice; aluminum oxide has stable performance and can protect the material to reduce side reactions; magnesium doping occupies the lithium position to improve the ionic conductivity of the material. When isopropoxide is doped as a metal ion dopant, a hydrolysis reaction occurs during the ball milling process, and the generated product is evenly coated on the precursor.
[0065] In some embodiments, in step (2), the drying temperature is 60-100° C.; the drying is performed by oven drying.
[0066] In some embodiments, in step (3), the sintering temperature is 500-800°C, specifically, for example, 500°C, 600°C, 700°C, 800°C; the sintering time is 8-36h, specifically, for example, 8h, 10h, 12h, 18h, 24h, 30h, 36h;
[0067] Optionally, the protective atmosphere includes nitrogen; Optionally, the sintering is performed in a nitrogen-protected furnace;
[0068] Optionally, the dried mixture is pre-fired in a protective atmosphere, ground after cooling, and then sintered in a protective atmosphere; the pre-fired temperature is 500-600°C, specifically, for example, 500°C, 550°C, 600°C; the pre-fired time is 12-24h, specifically, for example, 12h, 18h, 24h; optionally, the grinding is performed by sand milling, and the sand milling is performed by a sand mill; the grinding time is 2-3h; the sintering temperature is 600-800°C, specifically, for example, 600°C, 700°C, 800°C; the sintering time is 8-12h, specifically, for example, 8h, 10h, 12h; optionally, the sintering temperature is higher than the pre-fired temperature;
[0069] Optionally, the sintered product is cooled to room temperature in the furnace; optionally, the sintered product is cooled to room temperature in the furnace and pulverized to obtain carbon-coated lithium iron phosphate; optionally, the pulverization is performed by gas crushing.
[0070] In the embodiment of the present invention, pre-sintering is performed first and then sintering is performed, and the sintering temperature is higher than the pre-sintering temperature. The reaction is carried out step by step. The pre-sintering allows the doped ions and carbon to be coated on the surface of the precursor first, and then the high-temperature sintering is beneficial to the growth of lithium iron phosphate grains.
[0071] A carbon-coated lithium iron phosphate according to an embodiment of the present invention is prepared by the preparation method according to an embodiment of the present invention. In the embodiment of the present invention, the carbon-coated lithium iron phosphate has higher electrical conductivity and lower powder resistance, and can improve the energy efficiency of the battery.
[0072] In some embodiments, the particle size of the carbon-coated lithium iron phosphate is 0.3-2.0 μm, specifically, for example, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.5 μm, 2.0 μm.
[0073] In some embodiments, the mass percentage of carbon in the carbon-coated lithium iron phosphate is 0.5-2%, specifically, for example, 0.5%, 1%, 1.3%, 1.5%, 2%; wherein the mass percentage of fullerene in the carbon-coated lithium iron phosphate is 0.5-2%, specifically, for example, 0.5%, 1%, 1.3%, 1.5%, 2%; the mass percentage of metal doping elements in the carbon-coated lithium iron phosphate is 0-0.5%, specifically, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%; the mass percentage of lithium element in the carbon-coated lithium iron phosphate is 4-5%, specifically, for example, 4%, 4.5%, 5%; the carbon In the coated lithium iron phosphate, the mass percentage of iron element is 30-38%, specifically, for example, 30%, 32%, 34.5%, 36%, 38%; the molar ratio of lithium element, iron element and metal doping element is 1.0-1.08:0.95-0.99:0-0.05; specifically, 1.0-1.08 (for example, 1.00, 1.02, 1.05, 1.08):0.95-0.99 (for example, 0.95, 0.96, 0.97, 0.98, 0.99):0-0.05 (for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05), optionally, 1.05:0.98:0.02.
[0074] A lithium battery according to an embodiment of the present invention comprises a positive electrode material, wherein the positive electrode material comprises the carbon-coated lithium iron phosphate according to an embodiment of the present invention. In the embodiment of the present invention, the carbon-coated lithium iron phosphate has higher electrical conductivity and lower powder resistance, and can improve the energy efficiency of the battery.
[0075] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0076] Example 1
[0077] A method for preparing carbon-coated lithium iron phosphate comprises the following steps:
[0078] (1) 9.0 g of fullerene C 60 Dissolve in 1.8L o-xylene to obtain a fullerene solution, mix 739.02g of iron phosphate precursor (particle size 100-500nm) with the fullerene solution, heat in a water bath at 60°C, and stir evenly at a speed of 200r / min for 3 hours; filter the mixed slurry, wash, dry, and sieve to obtain a fullerene-coated iron phosphate precursor;
[0079] (2) mixing the fullerene-coated iron phosphate precursor with 7.99 g titanium dioxide, 369.45 g lithium carbonate, 18.0 g glucose, 18.0 g PEG, and 17.0 g conductive carbon black in deionized water, ball milling for 5 hours to obtain a mixture, and drying the mixture at 80° C.;
[0080] (3) The dried mixture is placed in a nitrogen protection furnace, pre-fired at 600° C. for 12 hours, ground and pulverized after cooling, sintered at 780° C. for 12 hours, cooled to room temperature with the furnace, and pulverized to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0081] The powder resistivity of the carbon-coated lithium iron phosphate positive electrode material is 23.05Ω·cm. At 25°C, the 2C soft pack discharge capacity is 2.75Ah and the discharge gram capacity is 133.49mAh / g.
[0082] Example 2
[0083] The preparation method is the same as that of Example 1, except that in step (1), the amount of fullerene used is 18.0 g; and in step (2), the amount of conductive carbon black used is 8.0 g.
[0084] Example 3
[0085] The preparation method is the same as that of Example 1, except that in step (2), 7.99 g of titanium dioxide is replaced by 20.4 g of aluminum isopropoxide.
[0086] Example 4
[0087] The preparation method is the same as that of Example 1, except that in step (2), 7.99 g of titanium dioxide is replaced by 4.0 g of magnesium oxide.
[0088] Example 5
[0089] The preparation method is the same as that of Example 1, except that in step (2), 7.99 g of titanium dioxide is replaced by 11.6 g of ammonium metavanadate.
[0090] Comparative Example 1
[0091] The preparation method is the same as that of Example 1, except that step (1) is omitted. In step (2), 739.02 g of iron phosphate precursor, 7.99 g of titanium dioxide, 369.45 g of lithium carbonate, 18.0 g of glucose, 18.0 g of PEG, and 26.0 g of conductive carbon black are mixed in deionized water and ball-milled for 5 hours to obtain a mixture, and the mixture is dried at 80°C.
[0092] Comparative Example 2
[0093] The preparation method is the same as that of Example 1, except that in step (1), o-xylene is replaced by deionized water.
[0094] Comparative Example 3
[0095] The preparation method is the same as that of Example 1, except that the mixing step in step (1) is omitted, and in step (2), 739.02 g of iron phosphate precursor, 9.0 g of fullerene C 60 Directly mix with 7.99 g titanium dioxide, 369.45 g lithium carbonate, 18.0 g glucose, 18.0 g PEG, and 17.0 g conductive carbon black in deionized water.
[0096] Comparative Example 4
[0097] The preparation method is the same as that of Example 1, except that in step (1), fullerene C 60 Replaced by graphene.
[0098] Comparative Example 5
[0099] The preparation method is the same as that of Example 1, except that titanium dioxide is omitted in step (2).
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that the carbon-coated lithium iron phosphate materials prepared by the preparation method of the present invention in Examples 1-5 have lower powder resistivity and better discharge capacity.
[0103] In Comparative Example 1, conductive carbon black was used to replace the closed fullerene C 60 Compared with Example 1, the powder resistance of the carbon-coated lithium iron phosphate material in Comparative Example 1 is higher and the discharge capacity is relatively lower.
[0104] In Comparative Example 2, the fullerene solution uses solvent water, the powder resistance increases, and the discharge capacity decreases. This is because the fullerene solution uses water as a solvent. The physical and chemical properties of fullerene and water are completely different, and the affinity between them is very weak. Excessive water molecules will reduce their affinity and affect their own properties, thereby causing performance degradation, which is not conducive to the coating of the iron phosphate precursor by fullerene, resulting in an increase in powder resistance and a decrease in discharge capacity.
[0105] In Comparative Example 3, the step of coating the iron phosphate precursor with fullerene is omitted, and fullerene is directly used for mixing, resulting in poor fullerene coating effect, increased powder resistance, and reduced discharge capacity.
[0106] In comparative example 4, graphene is used to replace the closed fullerene C 60 Compared with Example 1, the powder resistance of the carbon-coated lithium iron phosphate material in Comparative Example 4 is higher and the discharge capacity is relatively lower.
[0107] The carbon-coated lithium iron phosphate material in Comparative Example 5 does not contain metal doping elements. At this time, relative to Example 1, the powder resistance of the material is higher and the discharge capacity is relatively lower. This is because the metal doping elements in the carbon-coated lithium iron phosphate material can replace iron sites, forming lattice distortion and other lattice defects, thereby improving the ionic conductivity and electronic conductivity of the carbon-coated lithium iron phosphate.
[0108] from Figure 1 It can be seen that the fullerene C in Example 2 60 sp-doped carbon-coated lithium iron phosphate material 2 The hybrid orbital ratio is good, and the fullerene is uniformly coated at the molecular level, which can give full play to the fullerene SP 2 The conductivity of orbital hybridization improves the conductivity of carbon-coated lithium iron phosphate materials, reduces the powder resistance of the materials, and improves the energy efficiency of the battery.
[0109] from Figure 2 It can be seen that the fullerene C in Example 1 and Example 2 60 Batteries made of doped carbon-coated lithium iron phosphate materials have low internal resistance.
[0110] from Figure 3 It can be seen that the fullerene C in Example 1 and Example 2 60 Batteries made of doped carbon-coated lithium iron phosphate materials have less polarization under high-rate discharge.
[0111] from Figure 4 It can be seen that the fullerene C in Example 1 and Example 2 60 Batteries made of doped carbon-coated lithium iron phosphate materials have high energy efficiency.
[0112] from Figure 5It can be seen that the fullerene C in Example 1 and Example 2 60 Batteries made of doped carbon-coated lithium iron phosphate materials have good cycling performance.
[0113] from Figure 6 It can be seen that the fullerene C in Example 1 and Example 2 60 The discharge voltage platform of the battery made of doped carbon-coated lithium iron phosphate material is higher.
[0114] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0115] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing carbon-coated lithium iron phosphate, characterized in that: The following steps are involved: (1) mixing an iron phosphate precursor and a fullerene solution, and then drying the mixture to obtain a fullerene-coated iron phosphate precursor; wherein the solvent of the fullerene solution is a non-aqueous solvent; (2) mixing the fullerene-coated iron phosphate precursor, a lithium source, a metal ion dopant and a carbon source and ball milling the mixture to obtain a mixture, and drying the mixture; the metal ion dopant includes a metal doping element; (3) Sintering the dried mixture under a protective atmosphere to obtain carbon-coated lithium iron phosphate.
2. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (1), the solvent of the fullerene solution includes at least one of xylene, toluene or chlorobenzene.
3. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (1), the particle size of the iron phosphate precursor is 100-500 nm; and / or, the mass ratio of the iron phosphate precursor to fullerene is 97-100:0.01-3; And / or, the mixing is carried out under heating conditions; the mixing temperature is 40-80° C.; and the mixing time is 2-3 hours.
4. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (2), the molar ratio of the lithium element in the lithium source, the iron element in the fullerene-coated iron phosphate precursor, and the metal doping element in the metal ion dopant is 1.0-1.08:0.95-0.99:0-0.05; And / or, in the mixture of the fullerene-coated iron phosphate precursor, the lithium source, the metal ion dopant and the carbon source, the mass percentage of the carbon source is 3%-10%; And / or, the ball milling time is 3 to 7 hours.
5. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (2), the lithium source includes at least one of lithium hydroxide and lithium carbonate; And / or, the carbon source includes at least one of glucose, phenolic resin, sucrose, citric acid, polyethylene glycol, and conductive carbon black.
6. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (2), the metal doping element includes at least one of aluminum, titanium, magnesium, and vanadium; And / or, the metal ion dopant includes at least one of an oxide, a hydroxide, and a salt of a metal doping element.
7. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: In the step (3), the sintering temperature is 500-800°C; And / or, the sintering time is 8-36h; And / or, the particle size of the carbon-coated lithium iron phosphate is 0.3-2.0 μm.
8. The method for preparing carbon-coated lithium iron phosphate according to claim 7, characterized in that: In the step (3), the dried mixture is first pre-fired in a protective atmosphere, ground after cooling, and then sintered in a protective atmosphere; the pre-fired temperature is 500-600°C; the pre-fired time is 12-24h; the sintered temperature is 600-800°C; and the sintered time is 8-12h.
9. A carbon-coated lithium iron phosphate, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: It comprises a positive electrode material, wherein the positive electrode material comprises the carbon-coated lithium iron phosphate according to claim 9.
Citation Information
Patent Citations
Preparation method for low-resistivity lithium iron phosphate / carbon composite material
CN105742590A
Anti-air-expansion lithium titanate anode material dedicated to lithium battery and preparation method thereof
CN109301205A
Synthetic method for high-compacting lithium iron phosphate of football-like alkene frame-type construction
CN109626348A
Preparation method of nanoscale lithium iron phosphate
CN112599775A
Preparation method of lithium iron phosphate positive electrode material doped with nanometer titanium dioxide
CN113991112A
Cited By
Solid electrolyte precursor, solid electrolyte and preparation method thereof, and battery
CN119751058A
Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN120622449A
Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN120622449B